PROBLEMS OF DEVELOPMENT OF THE GREAT SILK ROAD IN THE GEOPOLITICAL REGION OF CENTRAL ASIA - M.S., Abdullaev (Journal of Geography, Regional Planning and Development, 2025)
Objective: This article examines the challenges and opportunities involved in revitalizing the Great Silk Road within the geopolitical context of Central Asia, focusing on its potential to enhance regional connectivity, economic development, and cultural exchange. Method: Employing a qualitative historical and geopolitical analysis, the study synthesizes archival records, policy documents, and international cooperation initiatives, such as UNESCO programs and the TRACECA corridor, to assess the strategic significance of Silk Road restoration. Results: Findings reveal that despite Central Asia’s central role in the historic Silk Road network, modern geopolitical constraints—especially limited access to global maritime routes—impede regional integration. However, recent infrastructure projects, including the Tejen-Serahs-Mashhad railway and the Andijan-Kashgar route, alongside coordinated multilateral efforts, demonstrate practical steps toward reinvigorating trade and diplomacy. Novelty: The article contributes a comprehensive, multi-dimensional perspective by bridging historical insights with contemporary political developments, highlighting Uzbekistan’s pivotal role in connecting continents through strategic policy and infrastructure. This integrated approach advances understanding of the Silk Road’s revival as a catalyst for international tourism, regional cooperation, and global trade, offering valuable implications for scholars and policymakers engaged in Central Asian geopolitics and economic strategy.